2014
DOI: 10.1021/am405329g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Diabetic Wound Repair Using Biodegradable Nanofibrous Metformin-Eluting Membranes: in Vitro and in Vivo

Abstract: This work developed biodegradable nanofibrous drug-eluting membranes that provided sustained release of metformin for repairing wounds associated with diabetes. To prepare the biodegradable membranes, poly-d-l-lactide-glycolide (PLGA) and metformin were first dissolved in 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) and were spun into nanofibrous membranes by electrospinning. An elution method and an HPLC assay were utilized to characterize the in vivo and in vitro release rates of the pharmaceuticals from the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 31 publications
1
54
0
2
Order By: Relevance
“…Diabetes has been shown to impair immune function and decrease wound healing, both of which are critical to survival and recovery from major wound injury . Furthermore, hyperglycemia is a risk factor for epithelial down growth following skin injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes has been shown to impair immune function and decrease wound healing, both of which are critical to survival and recovery from major wound injury . Furthermore, hyperglycemia is a risk factor for epithelial down growth following skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has been shown to impair immune function and decrease wound healing, both of which are critical to survival and recovery from major wound injury. 10 Furthermore, hyperglycemia is a risk factor for epithelial down growth following skin injury. A previous study demonstrated that Bixin promotes hypoglycemic activity 21 and mouth wound healing, 19 as well as improves the antioxidant response in different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a bioengineering group recently demonstrated that biodegradable nanofibrous drug-eluting membranes designed to sustainably release metformin, accelerated epithelization in wounds of STZ-injected diabetic rats. Specifically, the metformin-eluting membrane induced an 85% vs. 67% wound closure by day 7 and 97% vs. 85% closure by day 14 compared to non-eluting membrane treated wounds (Lee, Hsieh et al 2014). In addition, there is a large on-going Phase II clinical trial studying whether oral metformin (1000 mg three times a day) can help wound healing on burned children with expected results in 2017.…”
Section: Metforminmentioning
confidence: 99%
“…Further, PLGA forms nontoxic end products, increases wettability, and promotes cell proliferation. Lee et al [47] used PLGA polymer for incorporating metformin, an antihyperglycemic agent usually prescribed for treating type 2 diabetes. The prepared metformin-incorporated PLGA nanofiber was investigated to treat wounds in diabetic SD rat model.…”
Section: Synthetic Polymer Nanofibers As Wound Healing Scaffoldsmentioning
confidence: 99%